2021
DOI: 10.1007/s00787-021-01772-z
|View full text |Cite|
|
Sign up to set email alerts
|

Response (minimum clinically relevant change) in ASD symptoms after an intervention according to CARS-2: consensus from an expert elicitation procedure

Abstract: The lack of consensual measures to monitor core change in Autism Spectrum Disorder (ASD) or response to interventions leads to difficulty to prove intervention efficacy on ASD core symptoms. There are no universally accepted outcome measures developed for measuring changes in core symptoms. However, the CARS (Childhood Autism Rating Scale) is one of the outcomes recommended in the EMA Guideline on the clinical development of medicinal products for the treatment of ASD. Unfortunately, there is currently no cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
(37 reference statements)
0
13
1
Order By: Relevance
“…Further, a recent study has suggested that clinicians on an average would like to see a 4.5-point improvement to conclude to a meaningful improvement after an intervention in the context of ASD. 19 In this study, only a three-point improvement was observed after Nichi-Glucan supplementation. However, this is only a pilot study, and larger randomised, multi-centric clinical trials of longer duration for validation to attain a clinical meaningful response and to overcome the above-mentioned limitations are warranted.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Further, a recent study has suggested that clinicians on an average would like to see a 4.5-point improvement to conclude to a meaningful improvement after an intervention in the context of ASD. 19 In this study, only a three-point improvement was observed after Nichi-Glucan supplementation. However, this is only a pilot study, and larger randomised, multi-centric clinical trials of longer duration for validation to attain a clinical meaningful response and to overcome the above-mentioned limitations are warranted.…”
Section: Discussionmentioning
confidence: 52%
“…An improvement on the CARS by at least 4.5 points. 19 The CARS was monitored at baseline and after 90 days between the Gr.1 (control) and Gr.2 (Nichi Glucan). The CARS score was calculated based on a cumulative score obtained on the CARS scale, wherein a score below 30 indicates absence of sufficient signs and symptoms indicative of autism, a score between 30 and 36 indicates mildto-moderately severe autism, and a score from 37 to 60 is correlated with severe autism.…”
Section: Primary Endpointsmentioning
confidence: 99%
“…In particular, in four out of seven studies, CARS was applied. The validity of CARS has been demonstrated in a variety of studies in children of all ages [ 33 , 34 ]. Significant improvements in CARS scoring were evident in all papers included in our review [ 25 , 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…CARS-2 is a widely employed and validated tool for assessing ASD symptom burden [ 33 , 34 ]. Based on our review, we believe CARS-2 could be an effective quick, and nimble instrument to monitor changes in AD core symptoms over time.…”
Section: Proposal For a Shared Protocol (Figure 3)mentioning
confidence: 99%
See 1 more Smart Citation